CMMI and IDEAL in software process improvement - Bayona-Oré, Sussy (2020)
Different models and standards have been developed with the purpose of improving software development processes and obtaining quality products and achieving customer satisfaction. Despite the efforts that organizations make, they do not always achieve these results. In this article we present the results of the implementation of best practices established by the CMMI model using the IDEAL and SCAMPI B methodology. The results show that applying best practices helps organizations to improve their processes, minimize the number of defects and increase customer satisfaction. Likewise, the critical factors that were considered and aspects to be considered in the deployment of processes are presented. © 2020, World Scientific and Engineering Academy and Society. All rights reserved.